Relevansi Amsal 1:8-15 terhadap Peran Keluarga dalam Pembentukan Karakter Anak di Era Digital - Lewar, Agustinus Denny; Satang, Antonius; Dhogo, Petrus Cristologus; Manilet, Abraham Daud A. (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The formation of a child's character is an important task for parents. Character formation in children is not an easy task but rather a very complex one. Parents are required to help their children when they experience difficulties in developing good character within themselves at some point. Here, the role of parents is very much needed. In the current digital era, children are being challenged, where they face an era that creates dilemmas for them. This dilemma arises when children follow the flow of technological development or adhere to their parents' teachings. Therefore, the author highlights a holy scripture, namely Proverbs 1:8-15, to help parents understand how they should enlighten their children when they are facing challenges and trials in the digital era. This verse from the holy scripture also helps children to be able to stand firm in their beliefs, meaning they are not easily swayed by the changes of the times. The methods used in the writing of this scientific paper are library research and field research. The purpose of the research is to determine the extent to which parents play a role in the formation of a child's character. From the research conducted by the researchers at SDK St. Klaus Werang, it shows that the presence of gadgets in children has a positive influence on the formation of children's character. Although the presence of gadgets has had a significantly positive impact on the formation of children's character, parents must continue to monitor and limit their children's use of gadgets.